Work Attachment and Performance of Certain Functional Officers in Organizational Transition: Transformational Leadership as Moderation - Trisnawati, Ike; Sukmawati, Anggraini (Ridwan Institute, 2023)
The purpose of this study is to analyze the effect of work attachment and transformational leadership on the performance of certain functional officials during the organizational transition period and to identify the variables that most influence the performance of certain applicable officials during organizational transition. The data analysis used in this study is SEM with a Partial Least Square (PLS) approach. The SEM-PLS method was used to estimate the effect of work attachment and transformational leadership variables on performance. This study was conducted using a purposive sampling method on 51 samples of certain functional officials at the Center for Marine and Fisheries Socioeconomic Research. The results of the SEM-PLS test showed that work stickiness did not have a significant positive effect on the performance of functional officials. Work attachment has a significant positive impact on transformational leadership. Transformational leadership has a significant positive effect on the performance of available officials.